2012
DOI: 10.1016/j.jmb.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Dimensional Structural Basis of Type II Hyperprolinemia

Abstract: Type II hyperprolinemia is an autosomal recessive disorder caused by a deficiency in Δ1-pyrroline-5-carboxylate dehydrogenase (P5CDH, aka ALDH4A1), the aldehyde dehydrogenase that catalyzes the oxidation of glutamate semialdehyde to glutamate. Here we report the first structure of human P5CDH and investigate the impact of the hyperprolinemia-associated mutation of Ser352 to Leu on the structure and catalytic properties of the enzyme. The 2.5 Å resolution crystal structure of human P5CDH was determined using ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(104 citation statements)
references
References 46 publications
5
99
0
Order By: Relevance
“…1A) and Ser 340 ) enzymes, in which the specific residues are likely to be involved in catalytic processes, as reported previously in archaea and human orthologs (Fig. 1A) (25,66).…”
Section: Identification and In Silico Analysis Of Tcp5cdh-a 1686-bpsupporting
confidence: 76%
See 1 more Smart Citation
“…1A) and Ser 340 ) enzymes, in which the specific residues are likely to be involved in catalytic processes, as reported previously in archaea and human orthologs (Fig. 1A) (25,66).…”
Section: Identification and In Silico Analysis Of Tcp5cdh-a 1686-bpsupporting
confidence: 76%
“…DFT calculations also indicate that the imino-protonated cyclic form (P5C) is thermodynamically preferred over the zwitterionic form of ␥GS. Accordingly, crystallographic data indicate that ␥GS is the substrate of T. thermophilus ⌬ 1 -pyrroline-5-carboxylate dehydrogenase and that the nucleophilic attack of the thiol portion of Cys 336 to the ␥GS carbonyl yields an intermediate hemithioacetal, which is subsequently converted to glutamate via NAD ϩ -mediated hydrolysis (25,66). Assuming that the active site of the T. cruzi P5CDH is similar to that of T. thermophilus, the deprotonation of the -SH group of the cysteine residue (whose pK a is unknown but can be assumed to be ϳ6 -8) (81) might be crucial to the oxidation of ␥GS because the thiolate is a more efficient nucleophile than its corresponding protonated form.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of monofunctional human P5CDH has been established (18,19), ours is the first such study for PutAs.…”
Section: Discussionmentioning
confidence: 96%
“…Stopped flow methods demonstrated that the oxidative half-reaction with CoQ 1 is rate-limiting in the PRODH reaction (17). Although the kinetic mechanism of the P5CDH domain has yet to be fully characterized in EcPutA, it likely follows an ordered ternary mechanism as described for human P5CDH (18,19).…”
mentioning
confidence: 97%
“…Next, PRODH transfers two electrons from reduced flavin to an electron acceptor such as ubiquinone in the inner membrane of the mitochondria (or cytoplasmic membrane in prokaryotes) (86,135). After P5C spontaneously converts into GSA, GSA is oxidized to L-glutamate by P5C dehydrogenase (P5CDH) using nicotinamide adenine dinucleotide as an electron receptor (6,121). Glutamate generated by proline oxidation enters the tricarboxylic acid cycle after enzymatic conversion to a-ketogluturate.…”
Section: Ornithine-d-aminotransferasementioning
confidence: 99%